Supporting cells regulate the remodelling of aminoglycoside‐injured organ of Corti, through the release of high mobility group box 1. Issue 6 (8th July 2013) - Ladrech, Sabine; Mathieu, Marc; Puel, Jean‐Luc; Lenoir, Marc
Abstract To examine whether an inflammatory process occurs in the amikacin‐poisoned cochlea, we investigated the presence of the cytokines tumour necrosis factor‐α (TNF‐α), interleukin (IL)‐1β, and IL‐10. No TNF‐α, IL‐1β or IL‐10 was detected in the cochlear perilymph after the loss of most auditory hair cells, indicating the absence of severe inflammation. In contrast, we observed a significant and temporary increase in the level of extracellular high mobility group box 1 (HMGB1), a late mediator of inflammation that also functions as a signal of tissue damage. This increase coincided with epithelial remodelling of the injured organ of Corti, and occurred concomitantly with robust and transient cytoplasmic expression of acetylated HMGB1 within the non‐sensory supporting cells, Deiters cells. Here, HMGB1 was found to be enclosed within vesicles, a number of which carried the secretory vesicle‐associated membrane‐bound protein Rab 27A. In addition, transient upregulation of receptor for advanced glycation end‐products (RAGE), an HMGB1 membrane receptor, was found in most epithelial cells of the scarring organ of Corti when extracellular levels of HMGB1 were at their highest. Altogether, these results strongly suggest that, in stressful conditions, Deiters cells liberate HMGB1 to regulate the epithelial reorganization of the injured organ of Corti through engagement of RAGE in neighbouring epithelial cells.